Cambridge handbook of qualitative digital research/ edited by - Simeonova, B.; Galliers, Robert D. ([ S.l.]: Cambridge University Press, 2023)
Big data and algorithmic decision-making have been touted as game-changing developments in management research, but they have their limitations. Qualitative approaches should not be cast aside in the age of digitalisation, since they facilitate understanding of quantitative data and the questioning of assumptions and conclusions that may otherwise lead to faulty implications being drawn, and - crucially - inaccurate strategies, decisions and actions. This handbook comprises three parts: Part I highlights many of the issues associated with 'unthinking digitalisation', particularly concerning the overreliance on algorithmic decision-making and the consequent need for qualitative research. Part II provides examples of the various qualitative methods that can be usefully employed in researching various digital phenomena and issues. Part III introduces a range of emergent issues concerning practice, knowing, datafication, technology design and implementation, data reliance and algorithms, digitalisation.
Keywords: Knowledge Management; Qualitative Research Methods; Databases and Data Mining